CONSEQUENCES OF “THE PASJANЕ AFFAIR” FOR THE SERBIAN POPULATION OF THE GNJILANЕ REGION - МИЛОШЕВИЋ, Мирослав С. (Heritage, 2024)
In the summer of 1907, Serbian Chetniks clashed with the Turkish army and local Albanians near village Pasjane southeast of Gnjilane. After heavy fighting, the Serbian company was defeated and the Albanians started to take revenge on the Serbian population. The consequences for the Serbian population were disastrous: murders, robberies, kidnappings, rapes, forced emigrations and more. The Kingdom of Serbia, through the Serbian consulates in Priština and Skopje, tried to prevent further atrocities. The Turkish authorities did not show the will to calm the rebelling Albanians. They didn't arrest or punish the Albanians. The only success was the signing of the agreement (besa) as a guarantee that the Albanians would not attack the Serbs. However, the Albanians did not keep their word. In such an atmosphere of fear and violence, many Serbian families had to seek salvation by emigrating to Gnjilane or to the Kingdom of Serbia. The Serbian people in and around Gnjilane represented a compact environment. The aspiration of the Muslim population was to break up that environment as much as possible and the ethnic image to prevail in their favor.
Keywords: Serbs, Albanians, Gnjilane, Old Serbia, Ottoman empire, the crimes